UMP’s innovative ways to help stroke-stricken patients - UMP, PNC (Pejabat Naib Canselor, 2016)
A team of Universiti Malaysia Pahang (UMP) researchers had come up with a technology-related research that produced a rehabilitation device designed for stroke-stricken patients undergoing physiotherapy.